Małe formy, wielkie sprawy. Deontologia a potoczność w przekazach audiowizualnych dostępnych na YouTube - Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Small Forms, Big Problems. Deontology and Commonness in the Audiovisual Texts Presented on the YouTube This article concerns YouTube as the helpful service from the deontological perspective. There are many texts created by different users in this service. Big part of them refer to ethical issues. These texts are small forms which reveal big existential problems. There are six main topics of the article. First part concerns chances and threats in using of Web 2.0; YouTube is an example of this phenomenon. Social services on the Internet help to spread the official discourses, but also unofficial discourses. That is why we can observe the proliferation of commonness as the pattern of thinking and acting. Second part of the article refers to the philosophy of personalism. This kind of relection is important in the context of the social services on the Internet. Third part reveals some cultural phenomenons depended on the morality and immediacy. Fourth part consists of the interpretation of the peculiar example. The audiovisual text titled: For Jonah Mowry. Whats going on? became the source of many ethical explanations. The author of the article treats YouTube as the space of drama in the another part. The personal relations among users are shown in the perspective of the texts which are presented on this medium – it is the last topic of this article.